Analysis of Dispersion of the Pollutant PM2.5 by the La Leña Poultry Shop with the Langrangian Model in the Province of Huancayo, 2020 - Camargo Hinostroza, Steve Dann (2024)
In the present work we seek to analyze the dispersion of the PM 2.5 pollutant by the "La Leña" poultry shop with the Langrangian model in the province of Huancayo in the year 2020, for this the dispersion of the PM2.5 pollutant was simulated with the Lagrangian Method and the GRAL model This is a model developed by the Technological University of Graz Switzerland that simulates atmospheric pollutants emitted by fixed sources, it was elaborated using meteorological data that were pre-processed according to the requirements of the GRAL program, the mathematical calculations of the estimation of the emission, exit velocity and volumetric flow, the minimum PM2.5 concentration was determined with 0.14523 μg/m3 of concentration in the same emission source, this is due to the speed and direction of the wind that disperses this pollutant from the same source, in the same way the highest concentration was registered, which was 0.82253 μg/m3 located in the Plaza Constitución. Likewise, it is concluded that according to the direction ofthe wind and therefore where there is more concentration is in the West Northwest zone of the fixed source of emission.